Suffering, Torture and public Space - Neira, Hernán (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
Ricœur asserts that the medical therapeutics and phenomenology interweave in the semiotics of suffering signs. This becomes manifest when some fundamental characteristics of suffering are reached and defined. This methodology allows decipher the locus of suffering in the city by means of an aesthetic of the sublime. Being suffering an experience, the analysis of the relation of suffering with the theory of sublime is not only legitimate but inevitable. This forces to consider suffering as something wider than an individual fact and to define it as a component of the public interest. During the analysis we will evaluate some steps of suffering, as: long term suffering in a medical context, animal suffering, torture, euthanasia and suicide, whenever the aim of the last one is to rise an emotion in the city.